1995
DOI: 10.2172/123195
|View full text |Cite
|
Sign up to set email alerts
|

Protocols of radiocontaminant air monitoring for inhalation exposure estimates

Abstract: DISCLAIMER DISCLAIMERPottions of this document may be illegible electronic image products. images are produced from the best available original document... PurposeMonitoring the plutonium and americium particle emissions from soils contaminated during atmospheric nuclear testing or due to accidental releases is important for several reasons. First, it is important to quantify the extent of potential human exposure from inhalation of alpha-emitting particles, which is the major exposure pathway from transuran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The detailed scope, responsibilities, and procedures were documented in a "Study Plan" that contains or refers to several different "Detailed Procedures", and is too long for this report. The air sampling procedures are described in Shinn (1995). The methods discussed here are the same, except for minor modifications as those reported in Shinn, Homan, and Robison (1997).…”
Section: Methodsmentioning
confidence: 99%
“…The detailed scope, responsibilities, and procedures were documented in a "Study Plan" that contains or refers to several different "Detailed Procedures", and is too long for this report. The air sampling procedures are described in Shinn (1995). The methods discussed here are the same, except for minor modifications as those reported in Shinn, Homan, and Robison (1997).…”
Section: Methodsmentioning
confidence: 99%
“…AIMSWeb has reported that alternate form reliability is greater than .89 and concurrent validity for grades one and two ranges from .35 to .50 across various standardized tests. The AIMSWeb computation CBM was used in this study because it is a multiskill general outcome measurement of computational objectives that are consistent with grade-level expectations (Shinn, 2013). In addition, the AIMSWeb computation CBM has been shown to be a good predictor of students' overall mathematics achievement (Fuchs et al, 2007).…”
Section: Screening Benchmark and Follow-up Testsmentioning
confidence: 99%